2021
DOI: 10.1021/acsaem.1c01676
|View full text |Cite
|
Sign up to set email alerts
|

A Reversible Anodizing Strategy in a Hybrid Electrolyte Zn-Ion Battery through Structural Modification of a Vanadium Sulfide Cathode

Abstract: Rechargeable aqueous Zn-ion batteries (ZiBs) have received significant attention owing to their low cost and environmental friendliness. The charge storage mechanism of ZiBs generally depends on the cationic redox conversion. The anodic redox conversion is still rare due to the lack of suitable cathode materials and electrolytes, which may impede the ZiB performance. The present investigation focuses on enhancing the ZiB performance through in situ involvement of disulfide redox chemistry from a patronite Mn-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(60 citation statements)
references
References 56 publications
1
59
0
Order By: Relevance
“…However, their practical application is constrained in terms of safety issues and high costs. Recently, rechargeable zinc-ion batteries (ZiBs) have shown broad prospects for large-scale stationary applications, owing to the low cost, high ionic conductivity, low reduction potential (−0.76 V vs SHE), and environmental friendliness. However, the aqueous ZiB exhibits a low working potential window due to the narrow water decomposition potential (1.23 V) at constant pH. There are several approaches available to improve the electrochemical stability window (ESW) of aqueous ZiBs, such as the use of “water-in-salt” electrolyte, polymer electrolyte, organic/aqueous electrolyte, and so forth. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their practical application is constrained in terms of safety issues and high costs. Recently, rechargeable zinc-ion batteries (ZiBs) have shown broad prospects for large-scale stationary applications, owing to the low cost, high ionic conductivity, low reduction potential (−0.76 V vs SHE), and environmental friendliness. However, the aqueous ZiB exhibits a low working potential window due to the narrow water decomposition potential (1.23 V) at constant pH. There are several approaches available to improve the electrochemical stability window (ESW) of aqueous ZiBs, such as the use of “water-in-salt” electrolyte, polymer electrolyte, organic/aqueous electrolyte, and so forth. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Frackowiak et al have introduced a dual pH aqueous electrolyte system (acidic and alkaline solution) considering the Nernst equation and Pourbaix diagram to overcome the thermodynamic limit of water decomposition potential. , According to the Nernst equation and Pourbaix diagram, the overpotentials of the hydrogen evolution reaction and oxygen evolution reaction (HER and OER) vary with the pH of the electrolyte. In order to improve the ESW, the alkaline electrolyte is used in an anode compartment and the acid electrolyte in a cathode compartment. On the contrary, the usage of organic co-solvents to aqueous electrolytes expands ESW for aqueous batteries and supercapacitors. Among the various available organic solvents, acetonitrile (ACN) is mostly used as an additive solvent owing to its wide ESW, low viscosity, high dielectric constant, and so forth. , A Zn­(ACN) 2 complex is formed in a Zn salt based on the ACN/water electrolyte, which promotes faster Zn 2+ ionic mobility by reducing the cation–anion interactions. , In addition, the Zn­(ACN) 2 complex formed a solid electrolyte interphase on the anode surface, which effectively prevents the water decomposition. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanadium tetrasulfide (VS 4 ) has been proposed as a potential electrode material as a result of the large interlamellar spacing (5.83 Å) and weak coulombic attraction with guest Mg 2+ to enhance the ion diffusion. , Unfortunately, unoptimized VS 4 cannot display excellent electrochemical properties as a result of poor conductivity and serious polarization . To overcome these intrinsic problems of VS 4 , various strategies have been adopted, such as designing special nanoscale morphologies, doping metal ions, and combining with conductive materials . Among them, synthesizing VS 4 /carbonaceous materials is recognized as one of the most promising strategies on account of the favorable stability and electrochemical properties. , …”
mentioning
confidence: 99%
“…The ex situ Raman analysis of the Zn anode demonstrated the characteristic peaks located at 258, 440, 522,566, 766, and 1035 cm –1 (Figure S13a). The peaks at 258 and 522, 440 and 566, and 766 and 1035 cm –1 were attributed to the ZnF2, ZnO, and V–O and V–O–V modes, respectively. The formation of ZnF 2 suggested a solid electrolyte interface on the anode surface by the reduction of (OTf) − anions under an applied potential. , The higher peak intensity of the ZnF 2 compared to the ZnO suggested that the solid electrolyte interface prevented the formation of Zn dendrites (Figure S13a). However, the peak intensity at 522 cm –1 for the Zn anode of the coin cell device was lesser compared to the solid-state device, confirming that the solid electrolyte interface formation was inhibited in the presence of free water molecules…”
Section: Resultsmentioning
confidence: 99%